9A.04: CARDIOVASCULAR RISK FACTOR PROFILE IN AN ITALIAN COHORT OF PATIENTS WITH RHEUMATOID ARTHRITIS. (June 2015) - Erba, G.; Grosso, G.; Valena, C.A.; Riva, M.; Allevi, E.; Betelli, M.; Facchetti, R.; Mancia, G.; Pozzi, M.R.; Grassi, G.
Abstract : Objective: Rheumatoid arthritis (RA) is a systemic inflammatory disease characterized by an elevated cardiovascular morbidity and mortality, but detailed informations on the risk score profile using different approaches, as well as on the major determinant(s) of the cardiovascular risk of these patients are scanty. Design and method: The present study reports data collected in a cohort of RA patients with CV risk score calculators Framingham and SCORE uncorrected or corrected according to European League against Rheumatism (EULAR) recommendations. Cardiovascular events were recorded during the 3 yrs follow-up, to determine the burden of CV morbidity and the relative impact of traditional CV risk factors and disease activity/severity. We enrolled in the study 198 pts, 77% females, age 65.0 ± 11.6 yrs (means ± SD), disease duration 13 ± 9 yrs. 76% of pts were RF +, 68% ACPA+ and 46% with erosive disease. 3% were smokers and 32% ex smokers. Mean BMI (24.6 ± 4.4), plasma levels of cholesterol (total, HDL, LDL), triglycerides and glucose and prevalence of smokers were comparable with those detected in the local general population, while the prevalence of hypertension and diabetes were significantly higher in both males and females. Results: Risk scores with Framingham were lower than in general population and comparable using SCORE, but the application of 1.5x correction factor for RA, as recommended by EULAR, modified these figures. The number of hypertensive and diabetic pts increased significantly (P<.0001/ .019) during the follow-up as well as the mean values of Framingham and SCORE (p < .015/.011). The MI and stroke prevalence were 5% and 2% respectively: the incidence rate/1000 person/year were 8.8 and 3.7 versus 2.7 and 2.6 in the general population. No relation was detectable between disease activity indices and CV events or risk scores. Conclusions: The present study provides evidence that 1) RA is associated with an increased CV morbidity even in the medium follow-up period, 2) risk score needs to be adjusted as by EULAR indications to obtain sensitive assessment of risk and 3) that hypertension represents a major CV risk factor in this population.